Constructive solution of coupled second order delay differential equations with variable coefficients - R. J. Villanueva; A. Hervas; M. V. Ferrer (International Journal of Mathematics and Mathematical Sciences)
In this paper, we study initial value problems for coupld second order delay differential equations with variable coefficients. By means of the application of the method of steps and the method of Frobenius, the exact solution of the problem is constrcted. Then, in a bounded domain, a finite analytic solution with error bounds is provided. Given an admissible error ϵ we give the number of terms to be taken in the infinite series exact solution so that the approximation error be smaller than in the bounded domain.